2021
DOI: 10.1038/s41467-021-21135-1
|View full text |Cite
|
Sign up to set email alerts
|

Construction of intracellular asymmetry and asymmetric division in Escherichia coli

Abstract: The design principle of establishing an intracellular protein gradient for asymmetric cell division is a long-standing fundamental question. While the major molecular players and their interactions have been elucidated via genetic approaches, the diversity and redundancy of natural systems complicate the extraction of critical underlying features. Here, we take a synthetic cell biology approach to construct intracellular asymmetry and asymmetric division in Escherichia coli, in which division is normally symme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 64 publications
(71 reference statements)
0
28
0
Order By: Relevance
“…The reporter was constitutively expressed in the cell; however, the level would be low due to destabilization via the C-end degron. PopZ, an oligomeric protein upstream in the C. crescentus polarity pathway, , was used as the polarized scaffold to reconstitute enzymatic functions; SpmXΔC, a fragment of the stalk-positioning factor that preserves a direct binding to PopZ in E. coli , , was used as the adaptor for recruitment. Both N (1–118) and C (119–242) halves of the TEV proteases were designed to fuse with the SpmXΔC adaptor.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The reporter was constitutively expressed in the cell; however, the level would be low due to destabilization via the C-end degron. PopZ, an oligomeric protein upstream in the C. crescentus polarity pathway, , was used as the polarized scaffold to reconstitute enzymatic functions; SpmXΔC, a fragment of the stalk-positioning factor that preserves a direct binding to PopZ in E. coli , , was used as the adaptor for recruitment. Both N (1–118) and C (119–242) halves of the TEV proteases were designed to fuse with the SpmXΔC adaptor.…”
Section: Resultsmentioning
confidence: 99%
“…When PopZ is present, TEV is reassembled and becomes functional at the PopZ pole, enabling a localized cleavage of the C-terminal degron and thus a polarized stabilization of the reporter (Figure b). We previously demonstrated that, in order to establish an intracellular asymmetry at the length scale of an E. coli cell, diffusion must be actively countered . Given this prior knowledge, DivIVA, a Bacillus subtilis oligomeric protein with a propensity to target negative membrane curvature, , was fused to GFP and used as the reporter in the design.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Self-assembly of the evolved T7 RNAP system (eRNAP) has been largely eliminated through series of directed evolution ( Pu, Zinkus-Boltz & Dickinson, 2017 ; Pu, Kentala & Dickinson, 2018 ). This eRNAP platform enables detecting protein interaction ( Dewey & Dickinson, 2020 ; Lin et al, 2021 ) and manipulating strength of interaction ( Zinkus-Boltz, DeValk & Dickinson, 2019 ; Dewey et al, 2021 ). ABA inducible CRISPR/Cas9 gene editing in mammalian cells has been demonstrated using this evolved split T7 RNAP system ( Pu, Kentala & Dickinson, 2018 ).…”
Section: Introductionmentioning
confidence: 99%